Pré-melhoramento de acessos de abóbora visando enriquecimento nutricional - Ribeiro, Rayanne Maria Paula (Universidade Federal Rural do Semi-Árido, 2019)
Concern about the growing increase in malnutrition in the world has provoked the development of studies on food biofortification with the intention of improving the quality of agricultural products through plant breeding. Pumpkin is considered an important source of provitamin “A” with high levels in carotenoids. There is variability regarding the total carotenoid content, allowing selection of promising accessions for use in breeding programs. Thus, the objective of this work was to evaluate pumpkin accessions from states of Northeastern Brazil aiming at nutritional enrichment. The experiment for indirect selection of total carotenoids and characterization of pumpkin accessions was conducted in the Experimental Vegetable Garden of the Department of Agronomic and Forest Sciences (DCAF), Center of Agricultural Sciences (CCA), Universidade Federal Rural do Semi-Árido (UFERSA), Mossoró-RN. The experimental design was in complete randomized blocks with two replications and three plants per plot. The treatments consisted of 51 accessions from the DCAF/CCA/UFERSA Cucurbitaceae germplasm collection and one commercial cultivar. After maturation, the fruits were harvested, and one fruit per plant was selected to evaluate fruit descriptors, colorimetry and total carotenoid content. The experiment of agronomic performance and nutritional quality in pumpkin germplasm, under the conditions of Mossoró-RN, was conducted at Rafael Fernandes Experimental Farm of UFERSA, Mossoró-RN. The experimental design was in complete randomized blocks with four replications and six plants per plot. The treatments consisted of ten genotypes, consisting of five local pumpkin varieties from Sergipe (VD01, VD03, VD04 e VD05) and Maranhão (VD02) state, two progenies under development by Embrapa Coastal Tablelands (CPATC01 e CPATC02), and three commercial cultivars (Cultivar Jacarezinho, Maranhão e Sergipana). After ripening, the fruits were harvested and sent to the Ecophysiology laboratory of Embrapa Coastal Tablelands - SE. One fruit per plant was selected to evaluate fruit descriptors and quantify total carotenoids. Thus, it was possible to verify the diversity among the accesses and determine the most promising ones. For the DCAF/CCA/UFERSA Cucurbitaceae germplasm collection, the pulp color intensity parameters and the hº angle indicated the possibility of indirect selection to select accessions with higher total carotenoid contents. The ABO22 access presented the highest total carotenoid content under the evaluation conditions of the experiment. The grouping allowed the discrimination of accessions belonging to the DCAF/CCA/UFERSA Cucurbitaceae germplasm collection. The variables that most contributed to the formation of the groups for quantitative variables were fruit length and flesh firmness, and fruit shape for qualitative variables. Regarding the agronomic performance and nutritional quality in pumpkin germplasm, it was found that genotype VDO04 showed higher total carotenoid content than the other genotypes. The grouping allowed the discrimination of genotypes, where the formation of the groups occurred mainly by the total carotenoid content for the quantitative variables and fruit shape for the qualitative variables
Keywords: Cucurbita moschata Duch; Carotenoides; Variabilidade; Biofortificação; Cucurbita moschata Duch; Carotenoids; Variability; Biofortification; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA